Assessment of the Quality of Antenatal and Postnatal Care Services in Primary Health Centres in Rural Nigeria - Okonofua, Friday Ehbodaghe; Yaya, Sanni; Omorodion, Blessing (THE NIGERIAN JOURNAL OF SOCIOLOGY AND ANTHROPOLOGY, 2020)
Maternal mortality ratio in Nigeria is estimated to be 512 deaths per 100,000 live births. As with other low-income countries, a higher proportion of these deaths occur among women living in rural areas and in poor communities where access to maternal health care is limited by several barriers including quality of care in health facilities. The objective of this study was to assess the quality of antenatal and postnatal care in Primary Health Centres (PHCs) in two rural Local Government Areas of Edo State in Southern Nigeria. The data were obtained from exit interviews with 177 women after completion of antenatal and postnatal care in eight randomly selected PHCs. The interview questionnaire was adapted from the 2017 results-based financing exit interviews conducted by the World Bank in collaboration with the Federal Ministry of Health and the National Bureau of Statistics. It consisted of questions on the treatment received by women. The data were analysed with descriptive statistics and logistic regression. The results showed the self-reporting by women of sub-optimal offerings of 20 signal antenatal treatments and 8 signal postnatal care treatments. Close to half (45.6%) of the respondents for antenatal care reported receiving sub-optimal antenatal treatments compared to about a third of postnatal care attendees. The predictors of sub-optimal offerings of standard PHC care included local government area, marital status and previous childbirths. We conclude that concerted actions by health providers and policymakers in the PHCs to develop policies and interventions will improve the quality of delivery of antenatal and postnatal services in rural PHCs in Nigeria.
Keywords: Nigeria; ACE: Reproductive Health Innovation; University of Benin; CERHI; Lorretta Favour C. Ntoimo; Julius Ogungbangbe; Antenatal care; Primary Health Centres; Postnatal Care; Rural Areas; Exit Interviews